Malnutrition, cachexia and sarcopenia as susceptibility factors for cardiovascular complications in patients with cancer - Papasotiriou, Ionas; Tentolouris, Anastasios; Ntanasis-Stathopoulos, Ioannis; Liontos, Michalis (Frontiers in Pharmacology, 2026)
Cancer remains a leading cause of morbidity and mortality, although cancer survivorship has increased impressively in the past decades. Patients with cancer often face cardiovascular complications, either due to cancer itself or due to anti-cancer therapy, that may affect their quality of life and survival. Several studies have examined possible risk factors for cardiovascular susceptibility and/or cancer treatment-related cardiotoxicity, and some of them found a link between nutritional status and cardiovascular complications. In this review, we discuss the role of malnutrition, sarcopenia and cachexia, as susceptibility factors for cardiovascular complications and cardiotoxicity in cancer. The limited evidence shows that poor nutritional status and sarcopenia or cachexia is related to a cardiovascular burden in this population, and with a higher risk for cancer treatment-related cardiotoxicity. This relation may be mediated through several mechanisms and pathways, including cardiac wasting. Nutritional interventions should be examined for their effectiveness in reducing cardiovascular complications in patients with cancer, alongside with novel drugs that can prevent both skeletal and cardiac muscle wasting.